Human papillomavirus (HPV) infectionin hiv positive women of Florianópolis, state of Santa Catarina, Brazil - Fedrizzi, Edison N; Laureano, Juliana K; Schlup, Cristiane; Campos, Maristela O; Menezes, Maria Elizabeth (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: HPV infection is the most prevalent sexually transmitted disease worldwide. The disease induced by this virus is dependent on several other factors that affect the host. The main factor is immunosuppression, mainly associated with HIV infection. Objective: research the presence of HPV infection (HPV DNA) in a group of HIV positive women and compare it with the HIV negative women group; analyse the prevalence of viral groups of oncogenic high-risk, low-risk; the relation between these findings to socioeconomic, demographic and behavioural characteristics, as well as variables related to HIV infection, such as CD4 level, viral load and HAART use. Methods: a total of 20 HIV positive and 99 HIV negative women were enrolled in a cross-sectional and descriptive study, where genital samples were analysed by the hybrid capture method for detection of HPV DNA. Other data from charts and from a questionnaire have been collected from the patients. Results: the prevalence of HPV infection was 70% among the HIV positive group, and 21.2% among the HIV negative group. High-risk HPV was found in 71.4% of HPV positive cases of both groups, and both viral types were found in 35.7% of HIV positive women. HPV infection was associated with age above 35 years, low education level, CD4 between 200 to 500 cells/mm3, and HAART use in HIV positive women. Other variables studied did not show any association with HPV infection. Conclusion: the prevalence of HPV was about 3.3 times higher among HIV positive women, and high-risk HPV types were the most prevalent virus.